Oral Presentations Abstracts: CLAIMS OF MEDICAL MALPRACTICE IN THE AGE OF INFORMATION TECHNOLOGY - HANGANU, Bianca; MANOILESCU, Irina Smaranda; IOAN, Beatrice Gabriela (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Introduction. Medical practice is almost constantly bending to new technologies, and in recent years, the health care system has been increasingly dominated by advances in information technology. Its use offers many advantages, but it also has its own risks. Material and method. The authors conducted a literature review to see to what extent the accessibility and effective use of information technology, i.e. electronic health records (EHR) influence risk of malpractice. Results. The literature refers both to how EHR use can prevent malpractice claims, and how it can increase their number. Thus, EHR can prevent medical errors and associated complaints by: instant access to complete patient information (including laboratory and imaging results); improving communication between medical team members; reducing drug errors (e.g. drug interactions, allergic reactions); prompt request for further investigations. However, the misuse of EHR can create new problems: inadequate training with errors from implementation and accommodation; automatic or unexpected deletion of the recommended medication; the temptation to use the information obtained previously and the circumvention of the stage of obtaining a new medical history or the temptation to copy and paste the information from the previous consultations to the current consultation - which will lead to the perpetuation of errors and omissions from the previous consultations; increased risk of privacy and confidentiality breach. Likewise, certain facilities that these systems allow may be ambivalent, and may both reduce or increase the risk of complaints, depending on how they are used: communication between doctor and patient through messages, including updating prescriptions and reporting symptoms that require prompt evaluation but at the same time, delay in response may dissatisfy the patient. Conclusions. The implementation of EHR brings many advantages, both for the patient and for the medical staff in terms of accessing information, facilitating communication and carrying out treatment plans, but the medical staff must be constantly aware of the risks involved, especially related to their proper use.